Cathode material, cathode and lithium secondary battery including same

JP2025506665AActive Publication Date: 2025-03-13LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024547903
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-15
Filing Date
2023-02-15
Publication Date
2025-03-13
Estimated Expiration
2043-02-15

AI Technical Summary

Benefits of technology

【0012】 本発明によるリチウム二次電池用正極材は、充放電過程で収縮および膨張挙動が互いに異なる2種の正極活物質を含み、これにより、応力(stress)を分散して、充放電によるクラックの発生が抑制されるようにした。これにより、本発明の正極材を適用すると、寿命特性および抵抗特性に優れたリチウム二次電池を製造することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025506665000001_ABST
    Figure 2025506665000001_ABST
Patent Text Reader

Abstract

The present invention relates to a first positive electrode active material and a second positive electrode active material, the first positive electrode active material comprising a lithium transition metal oxide in which a molar ratio of nickel among transition metals is 70 mol % or more, the second positive electrode active material comprising a lithium transition metal oxide in which a molar ratio of nickel among transition metals is lower by 25 mol % or more than a molar ratio of nickel among transition metals of the first positive electrode active material, an average particle size of primary particles constituting the second positive electrode active material is larger than an average particle size of primary particles constituting the first positive electrode active material, and D of the second positive electrode active material is 50 D of the first positive electrode active material 50 The present invention relates to a positive electrode material for a lithium secondary battery, which is smaller than
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0019797 filed on February 15, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.

[0002] The present invention relates to a positive electrode material, and a positive electrode and a lithium secondary battery containing the same. More specifically, the present invention relates to a positive electrode material that can achieve high structural stability and long life by containing two types of positive electrode active materials that are controlled to have different compositions, primary particle diameters, and particle size distributions, and to a positive electrode and a lithium secondary battery that contain the same. [Background technology]

[0003] A lithium secondary battery generally comprises a positive electrode, a negative electrode, a separator and an electrolyte, and the positive electrode and the negative electrode contain active materials capable of intercalating and deintercalating lithium ions.

[0004] Lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2 or LiMnO4, etc.), lithium iron phosphate compound (LiFePO4), etc. have been used as the positive electrode active material of lithium secondary batteries. Among them, lithium cobalt oxide has the advantages of high operating voltage and excellent capacity characteristics, but the raw material cobalt is expensive and the supply is unstable, making it difficult to commercially apply it to large-capacity batteries. Lithium nickel oxide has poor structural stability and it is difficult to achieve sufficient life characteristics. On the other hand, lithium manganese oxide has excellent stability but has a problem of poor capacity characteristics. In order to compensate for the problems of lithium transition metal oxides containing Ni, Co, or Mn alone, lithium composite transition metal oxides containing two or more transition metals have been developed, and among them, lithium nickel cobalt manganese oxide containing Ni, Co, and Mn is widely used.

[0005] Generally, lithium nickel cobalt manganese oxide is in the form of spherical secondary particles formed by agglomeration of tens to hundreds of primary particles, and thus, during the manufacturing of the positive electrode, not only is particle cracking likely to occur, in which the primary particles are separated from each other, during the rolling process, but also, when charging and discharging are repeated, the volume of the unit lattice changes due to the insertion and extraction of lithium ions, causing cracks to occur along the interface between the primary particles. When particle cracking or cracks occur in the positive electrode active material, the contact area with the electrolyte increases, which increases the generation of gas and the deterioration of the active material due to side reactions with the electrolyte, and this can result in a decrease in life characteristics.

[0006] Furthermore, in order to achieve high energy density, active attempts have been made recently to increase the Ni content in NCM-based lithium transition metal composite oxides. In this case, the high reactivity and anisotropic volume change of nickel increases the possibility of cracks occurring within the particles during charge and discharge, which may cause the structure to collapse and deteriorate the battery performance.

[0007] Therefore, there is a need to develop a positive electrode material that has excellent structural stability and exhibits high energy density. Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention is made to solve the above-mentioned problems, and aims to provide a positive electrode material for lithium secondary batteries that contains two types of positive electrode active materials that are controlled to have different compositions, primary particle diameters, and final particle diameters, thereby suppressing the occurrence of cracks and providing high structural stability.

[0009] Another object of the present invention is to provide a positive electrode and a lithium secondary battery having improved life characteristics and resistance characteristics by applying the above-mentioned positive electrode material. [Means for solving the problem]

[0010] According to one embodiment, the present invention provides a method for producing a lithium-transition metal oxide having a nickel molar ratio of 70 mol % or more among transition metals, and a lithium-transition metal oxide having a nickel molar ratio of 25 mol % or more lower than the nickel molar ratio of the transition metals of the first positive active material, the average particle size of primary particles constituting the second positive active material being larger than the average particle size of primary particles constituting the first positive active material, and the D of the second positive active material being 100% or more. 50 is D of the first positive electrode active material 50 The present invention provides a positive electrode material for lithium secondary batteries, which is smaller than

[0011] According to another embodiment, the present invention provides a positive electrode including the positive electrode material for a lithium secondary battery according to the present invention, and a lithium secondary battery including the positive electrode. Effect of the Invention

[0012] The cathode material for lithium secondary batteries according to the present invention includes two types of cathode active materials that have different contraction and expansion behaviors during charging and discharging, thereby dispersing stress and suppressing the occurrence of cracks due to charging and discharging. Therefore, by applying the cathode material of the present invention, a lithium secondary battery with excellent life characteristics and resistance characteristics can be manufactured. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 shows the results of operando XRD analysis of two positive electrode active materials having different nickel contents. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will now be described in more detail.

[0015] In the present invention, the term "primary particle" refers to a particle unit that does not have grain boundaries when observed at a magnification of 5,000 to 20,000 times using a scanning electron microscope. The term "average particle size of primary particles" refers to the arithmetic mean value calculated after measuring the particle sizes of at least 30 primary particles observed in a scanning electron microscope image. Here, the particle size refers to the diameter of the longest axis of the primary particle.

[0016] In the present invention, the "secondary particles" are particles formed by agglomeration of a plurality of primary particles.

[0017] In the present invention, "D of the positive electrode active material 50 " means the particle size corresponding to 50% of the volume cumulative particle size distribution of the positive electrode active material powder, and the final particle, i.e., when the positive electrode active material is composed of secondary particles, the D 50 The above D 50 can be measured using a laser diffraction method. For example, the positive electrode active material powder is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., MT 3000 manufactured by Microtrac), and ultrasonic waves of about 28 kHz are irradiated at an output of 60 W, and a volume cumulative particle size distribution graph is obtained, and the particle diameter at a point corresponding to 50% of the volume cumulative amount is obtained.

[0018] In the present invention, the "c-axis length of the positive electrode active material" may be measured by performing an Ex-Situ XRD analysis in a state where the positive electrode active material is sampled using a Be window and a kapton tape and is isolated from contact with moisture and air.

[0019] Cathode material In general, a positive electrode active material with a high nickel content has a greater degree of anisotropic contraction and expansion during charging and discharging compared to a positive electrode active material with a low nickel content. This increases the likelihood of cracks occurring within the particles, and the cracks transferred to the surface may cause the electrolyte to penetrate, resulting in structural deterioration of the positive electrode material and shortening the life of the battery.

[0020] In order to solve this problem, the present inventors have introduced a high-nickel positive electrode active material in which the nickel content is maximized to 70 mol % or more, and the nickel content is 25 mol % or more less than that of the high-nickel positive electrode active material, the particle size of the primary particles is large, and the D of the final particles is reduced. 50 They discovered that by mixing and using a low-nickel positive electrode active material with a small particle size, it is possible to achieve a balance between particle contraction / expansion during charging and discharging, thereby realizing a positive electrode material with high energy density and a low rate of cracking.

[0021] For example, referring to Fig. 1, in which the change in c-axis length was observed while charging and discharging coin half cells to which a high-nickel positive electrode active material (positive electrode active material A) and a low-nickel positive electrode active material (positive electrode active material B) were applied in Experimental Example 1 of the present application, it can be seen that the shrinkage / expansion behavior of the particles differs depending on the nickel content. The c-axis length indicates the interlayer distance within the primary particles of a layered structure, and at the end of charging (around 4.0V to 4.2V), the positive electrode active material A with a relatively high nickel content experiences large shrinkage, whereas the positive electrode active material B with a relatively low nickel content exhibits an expanding behavior, and conversely, at the beginning of discharge (around 4.0V to 4.2V), the positive electrode active material A experiences large expansion, whereas the positive electrode active material B exhibits a shrinking behavior.

[0022] That is, when positive electrode active materials with different nickel contents are used together, when the high-nickel positive electrode active material particles experience a large contraction at the end of charging, the positive electrode active material particles with a lower nickel content expand in comparison, applying compressive stress to the high-nickel positive electrode active material particles to prevent cracks from becoming larger, and at the beginning of discharge, the opposite effect is achieved to relieve the stress of the high-nickel positive electrode active material particles. However, since the range in which the high-nickel positive electrode active material particles contract / expand is larger than the range in which the low-nickel positive electrode active material particles expand / expand, it is necessary to balance this by increasing the particle size of the primary particles of the low-nickel positive electrode active material.

[0023] Meanwhile, since the second positive electrode active material has a relatively larger average particle size of the primary particles than the first positive electrode active material, the D 50 is D of the first positive electrode active material 50 In addition, since the second positive electrode active material has a relatively low nickel content compared to the first positive electrode active material, the D 50 is D of the first positive electrode active material 50 It is advantageous for the .DELTA..times ...

[0024] In addition, when the difference in nickel content between the first and second positive electrode active materials is 25 mol % or more, the particles expand and contract in a complementary manner during charging and discharging, making it easy to disperse stress. However, when the difference is less than 25 mol %, the particles of the two active materials expand and contract simultaneously, and the simultaneous expansion results in large stress and cracks. The occurrence of cracks accelerates as cycles are repeated, leading to a decrease in life characteristics.

[0025] Therefore, the cathode material according to the present invention includes a first cathode active material and a second cathode active material, the first cathode active material includes a lithium transition metal oxide in which the molar ratio of nickel among the transition metals is 70 mol % or more, the second cathode active material includes a lithium transition metal oxide in which the molar ratio of nickel among the transition metals is 25 mol % or more lower than the molar ratio of nickel among the transition metals of the first cathode active material, the average particle size of primary particles constituting the second cathode active material is larger than the average particle size of primary particles constituting the first cathode active material, and D of the second cathode active material is 50 is D of the first positive electrode active material 50 To provide a positive electrode material for a lithium secondary battery which is smaller than that of the

[0026] Specifically, the first and second positive electrode active materials can each include a lithium transition metal oxide containing nickel, cobalt, and manganese.

[0027] In one embodiment of the present invention, the first positive electrode active material may contain a lithium transition metal oxide in which the molar ratio of nickel among the transition metals is 80 mol % or more, preferably 85 mol % or more, and more preferably 90 mol % or more.

[0028] Meanwhile, the first positive electrode active material may include a lithium transition metal oxide represented by the following Formula 1:

[0029] [Chemical formula 1] Li 1+x (Ni a Co b Mn c M d )O2

[0030] In the above Chemical Formula 1, M is one or more selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo; x, a, b, c, and d are -0.2≦x≦0.2, 0.70≦a<1, 0 <b≦0.20、0<c≦0.20、0≦d≦0.10、a+b+c+d=1である。

[0031] The 1+x represents the lithium molar ratio in the lithium transition metal oxide and may be -0.1≦x≦0.2 or 0≦x≦0.2. When the lithium molar ratio satisfies this range, the crystal structure of the lithium transition metal oxide may be stably formed.

[0032] The a represents the molar ratio of nickel to all metals other than lithium in the lithium transition metal oxide, and may be 0.80≦a<1, 0.85≦a<1, 0.90≦a<1, or 0.92≦a<1. When the nickel molar ratio satisfies the above range, a high energy density is exhibited and a high capacity can be realized.

[0033] Said b represents the cobalt molar ratio among all the metals other than lithium in the lithium transition metal oxide, and can be 0 < b ≤ 0.15, 0 < b ≤ 0.10, 0 < b ≤ 0.08, or 0 < b ≤ 0.06. When the molar ratio of cobalt satisfies the above range, good resistance characteristics and output characteristics can be realized.

[0034] Said c represents the manganese molar ratio among all the metals other than lithium in the lithium transition metal oxide, and can be 0 < c ≤ 0.15, 0 < c ≤ 0.10, 0 < c ≤ 0.07 or 0 < c ≤ 0.05. When the molar ratio of manganese satisfies the above range, the positive electrode active material exhibits excellent structural stability.

[0035] Said d represents the molar ratio of the doping element among all the metals other than lithium in the lithium transition metal oxide, and can be 0 ≤ d ≤ 0.10, 0 ≤ d ≤ 0.08, 0 ≤ d ≤ 0.07 or 0 ≤ d ≤ 0.05.

[0036] In one embodiment of the present invention, the first positive electrode active material can contain one or more doping elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo. In this case, there is an advantage of being structurally stable in terms of crystal structure. Preferably, the first positive electrode active material can contain Al as the doping element. In other words, d can be 0 < d ≤ 0.10.

[0037] In one embodiment of the present invention, the second positive electrode active material can contain a lithium transition metal oxide in which the molar ratio of nickel among the transition metals is 40 mol% to 65 mol%, preferably 40 mol% to 60 mol%, and more preferably 50 mol% to 60 mol%.

[0038] On the other hand, the second positive electrode active material can contain a lithium transition metal oxide represented by the following Chemical Formula 2.

[0039] [Chemical Formula 2] Li 1+y(Ni e Co f Mn g M' h )O2

[0040] In the above Chemical Formula 2, M' is one or more selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo; where y, e, f, g, and h are −0.2≦y≦0.2, 0.40≦e≦0.65, 0.10≦f≦0.40, 0.10≦g≦0.40, 0≦h≦0.10, and e+f+g+h=1, respectively.

[0041] The 1+y represents the lithium molar ratio in the lithium transition metal oxide and may be -0.1≦y≦0.2 or 0≦y≦0.2. When the lithium molar ratio satisfies this range, the crystal structure of the lithium transition metal oxide may be stably formed.

[0042] The e represents a molar ratio of nickel among all metals other than lithium in the lithium transition metal oxide, and may be 0.40≦e≦0.60, 0.50≦e≦0.60, or 0.55≦e≦0.60. When the molar ratio of nickel satisfies this range, a certain or higher energy density can be exhibited to ensure capacity, and stress can be dispersed in accordance with the expansion / contraction behavior of the first positive electrode active material particles having a high nickel content.

[0043] The f represents a molar ratio of cobalt to all metals other than lithium in the lithium transition metal oxide, and is 0.10 <f≦0.40、0.10<f≦0.35、または0.15≦f≦0.30であることができる。

[0044] The g represents the molar ratio of manganese to all metals other than lithium in the lithium transition metal oxide, and is 0.10 <f≦0.40、0.10<f≦0.35、または0.15≦f≦0.30であることができる。

[0045] The h represents a molar ratio of the doping element to all metals other than lithium in the lithium transition metal oxide, and may be 0≦h≦0.10, 0≦h≦0.08, 0≦h≦0.07, or 0≦h≦0.05.

[0046] In one embodiment of the present invention, the second positive electrode active material may contain one or more doping elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and in this case, there is an advantage that the crystal structure is stable. Preferably, the second positive electrode active material may contain Zr as a doping element. In other words, the h is 0 <h≦0.10であることができる。

[0047] In one embodiment of the present invention, the average particle size of the primary particles constituting the first positive electrode active material may be 0.1 μm or more and 1 μm or less, preferably 0.2 μm or more and 0.7 μm or less. In this case, it is preferable in that both the capacity and the life can be satisfied.

[0048] The primary particles constituting the second positive electrode active material may have an average particle size of more than 1 μm and not more than 3 μm, preferably 1.5 μm or more and 2.5 μm or less, which is preferable in terms of satisfying both output and life.

[0049] The average particle size of the primary particles constituting the first and second positive electrode active materials can be adjusted by controlling the sintering conditions. In general, positive electrode active materials are manufactured by mixing a precursor, which is a transition metal hydroxide, with a lithium source and then sintering the mixture. The higher the sintering temperature and the longer the sintering time, the larger the particle size of the primary particles constituting the positive electrode active material particles. Therefore, the particle size of the primary particles constituting the positive electrode active material particles can be adjusted by adjusting the sintering temperature and / or sintering time during the manufacture of the positive electrode active material.

[0050] For example, the first positive electrode active material may be prepared by performing the sintering at a temperature of 650° C. to 800° C. for 5 hours to 20 hours, and the second positive electrode active material may be prepared by performing the sintering at a temperature of 800° C. to 950° C. for 5 hours to 20 hours.

[0051] In one embodiment of the present invention, the D of the first positive electrode active material 50 The D of the second positive electrode active material may be 8 μm or more and 20 μm or less, preferably 12 μm or more and 18 μm or less. 50 The D of the first positive electrode active material and the second positive electrode active material can be 1 μm or more and less than 8 μm, preferably 2 μm or more and 5 μm or less. 50 When the above range is satisfied, it is preferable in terms of maximizing the electrode density and balancing the volume expansion and contraction behavior.

[0052] In addition, the absolute value of the difference between the rate of change in the c-axis length of the first positive electrode active material according to the following formula 1 and the rate of change in the c-axis length of the second positive electrode active material according to the following formula 1 may be 0% to 10%, preferably 0% to 7%, and more preferably 0% to 3%. When the absolute value of the difference in the rate of change in the c-axis length of the two positive electrode active materials is in the above range, it is preferable in that stress between the two positive electrode active materials during charging and discharging can be alleviated.

[0053] [Formula 1] c-axis length change rate (%) = {(C o -C1 / C o )×100}

[0054] In the above formula 1, C o is the c-axis length of the positive electrode active material in an uncharged state, C1 is the c-axis length of the positive electrode active material in a charged state at 4.2 V.

[0055] The positive electrode material may contain the first positive electrode active material and the second positive electrode active material in a weight ratio of 50:50 to 99:1, preferably 70:30 to 90:10, and more preferably 60:40 to 90:10. In consideration of the nickel content, it is preferable that the first positive electrode active material is contained in a larger amount than the second positive electrode active material in order to achieve a high energy density.

[0056] Meanwhile, the first positive electrode active material and the second positive electrode active material according to the present invention may further include a coating layer on the surface of the lithium transition metal oxide particles, if necessary. Here, the coating layer may include one or more coating elements selected from the group consisting of Al, Ti, W, B, F, P, Mg, Ni, Co, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mn, Sr, Sb, Bi, Si, and S. When a coating layer is present on the surface of the lithium transition metal oxide, the coating layer reduces the contact between the electrolyte and the lithium transition metal oxide, thereby reducing the elution of the transition metal and the generation of gas due to side reactions with the electrolyte. Preferably, the coating layer may include B, Co, Al, or a combination thereof, and more preferably, may include Co. When the coating layer includes Co, it is possible to obtain the effects of suppressing side reactions with the electrolyte, as well as improving output and reducing resistance.

[0057] Meanwhile, the first and second positive electrode active materials may be prepared by the following method, but are not limited thereto.

[0058] The precursor for preparing the positive electrode active material may be a commercially available positive electrode active material precursor, or may be prepared by a method for preparing a positive electrode active material precursor known in the art.

[0059] For example, the precursor may be prepared by adding an ammonium cation-containing complex former and a basic compound to a transition metal solution containing a nickel-containing raw material, a cobalt-containing raw material, and a manganese-containing raw material, and then subjecting the mixture to a coprecipitation reaction.

[0060] The nickel-containing raw material may be, for example, a nickel-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and specifically may be, but is not limited to, Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, a fatty acid nickel salt, a nickel halide, or a combination thereof.

[0061] The cobalt-containing source material may be a cobalt-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and specifically may be, but is not limited to, Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, CoSO4, Co(SO4)2·7H2O, or a combination thereof.

[0062] The manganese-containing raw material may be, for example, manganese-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, oxyhydroxide, or a combination thereof, and specifically may be manganese oxides such as Mn2O3, MnO2, and Mn3O4; manganese salts such as MnCO3, Mn(NO3)2, MnSO4, manganese acetate, manganese dicarboxylate, manganese citrate, and manganese fatty acid salt; manganese oxyhydroxide, manganese chloride, or a combination thereof, but is not limited thereto.

[0063] The transition metal solution may be prepared by adding a nickel-containing raw material, a cobalt-containing raw material, and a manganese-containing raw material to a solvent, specifically, water or a mixed solvent of an organic solvent (e.g., alcohol, etc.) that can be uniformly mixed with water, or by mixing an aqueous solution of the nickel-containing raw material, an aqueous solution of the cobalt-containing raw material, and the manganese-containing raw material.

[0064] The ammonium cation-containing complexing agent may be, for example, but is not limited to, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, (NH4)2CO3, or a combination thereof. Meanwhile, the ammonium cation-containing complexing agent may be used in the form of an aqueous solution, and the solvent may be water or a mixture of water and an organic solvent (e.g., alcohol, etc.) that is uniformly miscible with water.

[0065] The basic aqueous solution may be an aqueous solution of a basic compound such as an alkali metal or alkaline earth metal hydroxide, such as NaOH, KOH, or Ca(OH)2, a hydrate thereof, or a combination thereof. Here, the solvent may be water or a mixture of water and an organic solvent (specifically, alcohol, etc.) that is uniformly miscible with water.

[0066] The basic aqueous solution is added to adjust the pH of the reaction solution, and may be added in an amount that allows the pH of the metal solution to be 9 to 12.

[0067] The above-mentioned transition metal-containing solution containing nickel, cobalt and manganese, precursor and hydroxide are mixed, and then an aqueous ammonia solution and an aqueous base solution are mixed to produce lithium transition metal hydroxide precursor core particles by coprecipitation reaction.

[0068] Here, the coprecipitation reaction can be carried out under an inert atmosphere such as nitrogen or argon at a temperature of 25°C to 60°C.

[0069] Thereafter, the nickel-based lithium transition metal hydroxide precursor is mixed with a lithium source material and, optionally, an aluminum source material, and then calcined.

[0070] The lithium source material may be a lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide, or oxyhydroxide, and is not particularly limited as long as it can be dissolved in water. Specifically, the lithium source material may be Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi, or Li3C6H5O7, and any one or a mixture of two or more of these may be used.

[0071] The calcination is carried out in an air or oxygen atmosphere, and the calcination temperature and time applied in the preparation of the first and second positive electrode active materials are as described above.

[0072] positive electrode Next, the positive electrode according to the present invention will be described.

[0073] The positive electrode according to the present invention includes the positive electrode material according to the present invention. Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, and the positive electrode active material layer includes the positive electrode material according to the present invention.

[0074] Since the positive electrode material has been described above, a detailed description thereof will be omitted, and only the remaining components will be described in detail below.

[0075] The positive electrode current collector may contain a metal having high conductivity, and may be any material that is easily attached to the positive electrode active material layer and is non-reactive within the voltage range of the battery. The positive electrode current collector may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like. The positive electrode current collector may generally have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0076] The positive electrode active material layer may optionally contain a conductive material and a binder, in addition to the positive electrode material, as necessary.

[0077] Here, the positive electrode material may be included in an amount of 80 to 99 wt %, more specifically 85 to 98.5 wt %, based on the total weight of the positive electrode active material layer, and excellent capacity characteristics can be exhibited when included in the above content range.

[0078] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery that is constructed and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; carbon-based materials such as carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive tubes such as carbon nanotubes; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and among these, one type alone or a mixture of two or more types can be used. The conductive material can be contained in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.

[0079] The binder serves to improve adhesion between the positive electrode particles and between the positive electrode and the current collector.Specific examples of the binder include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, polymethyl methacrylate, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and polymers in which hydrogen is substituted with Li, Na, or Ca, or various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be contained in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.

[0080] The positive electrode can be manufactured by a normal method for manufacturing a positive electrode, except for using the positive electrode material described above. Specifically, the positive electrode can be manufactured by applying a positive electrode mixture, which is manufactured by dissolving or dispersing the positive electrode material described above and, if necessary, a binder, a conductive material, and a dispersant in a solvent, onto a positive electrode current collector, followed by drying and rolling, or by casting the positive electrode mixture onto another support, followed by peeling it off from the support and laminating the resulting film onto a positive electrode current collector.

[0081] The solvent may be a solvent commonly used in the art, and may include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), dimethyl formamide (DMF), acetone, water, etc., and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, binder, and dispersant in consideration of the coating thickness of the slurry and the manufacturing yield, and to have a viscosity that can show excellent thickness uniformity when applied to manufacture a positive electrode.

[0082] Lithium secondary battery Next, the lithium secondary battery according to the present invention will be described.

[0083] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode facing the positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. Since the positive electrode is as described above, a detailed description thereof will be omitted, and only the remaining components will be described in detail below.

[0084] Also, the lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0085] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0086] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and may have fine irregularities formed on the surface of the current collector to enhance the binding force of the negative electrode active material, as in the case of the positive electrode current collector. For example, the negative electrode current collector may be used in various forms, such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0087] The negative electrode active material layer includes a negative electrode active material, and optionally a binder and a conductive material.

[0088] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β (0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. Also, a metallic lithium thin film may be used as the negative electrode active material.

[0089] The negative electrode active material may be included in an amount of 80% by weight to 99% by weight based on the total weight of the negative electrode active material layer.

[0090] The binder is a component that facilitates bonding between the conductive material, the active material, and the current collector, and is usually added in an amount of 0.1% by weight to 10% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0091] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of the conductive material include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0092] The negative electrode active material layer may be manufactured by coating a negative electrode mixture, which is prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent, on a negative electrode current collector and drying the coated negative electrode mixture. Alternatively, the negative electrode mixture may be cast on a separate support, and then peeled off from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0093] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery can be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. can be used. In addition, a coated separator containing a ceramic component or a polymeric material can be used to ensure heat resistance or mechanical strength, and can be selectively used in a single-layer or multi-layer structure.

[0094] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0095] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0096] The organic solvent can be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent can be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that can be used include carbonate-based solvents such as polycarbonate (PC) and polycarbonate-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can enhance the charge / discharge performance of a battery and a low-viscosity straight-chain carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred.

[0097] The lithium salt can be used without any particular limitation as long as it is a compound that can provide lithium ions used in lithium secondary batteries. Specifically, the anion of the lithium salt is F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - The lithium salt may be at least one selected from the group consisting of LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The lithium salt is preferably used in a concentration range of 0.1 to 4.0M. When the lithium salt concentration is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore excellent electrolyte performance can be exhibited, and lithium ions can be effectively transferred.

[0098] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethyl alcohol amine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethyl alcohol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. Here, the additives may be contained in an amount of 0.1 to 5 wt % based on the total weight of the electrolyte.

[0099] As described above, the lithium secondary battery including the bimodal cathode material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in portable devices such as mobile phones, notebook computers and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0100] According to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.

[0101] The battery module or the battery pack may be used as a power source for one or more medium- to large-sized devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0102] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.

[0103] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery in a medium- to large-sized battery module including a large number of battery cells.

[0104] Examples of the medium to large devices include, but are not limited to, electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0105] The present invention will now be described in more detail with reference to specific examples.

[0106] <Production Example: Production of Positive Electrode Active Materials A to G> Production Example 1 - Production of Positive Electrode Active Material A Ni 0.94 Co 0.04 Mn 0.02 (OH)2, LiOH and Al(OH)3 were mixed in amounts such that the molar ratio of (Ni+Co+Mn):Li:Al was 0.98:1.05:0.02. The mixed powder was placed in an alumina crucible and heat-treated at 720°C for 10 hours in an oxygen (O2) atmosphere to obtain Li[Ni 0.92 Co 0.04 Mn 0.02 Al 0.02 A positive electrode active material A represented by ]O2 was prepared.

[0107] Production Example 2 - Production of Positive Electrode Active Material B Ni 0.6 Co 0.2 Mn 0.2 (OH)2 and LiOH were mixed in amounts such that the molar ratio of (Ni+Co+Mn):Li was 1:1.05. The mixed powder was placed in an alumina crucible and heat-treated at 900°C for 15 hours in an oxygen (O2) atmosphere to obtain Li[Ni 0.6 Co 0.2 Mn 0.2 A positive electrode active material B represented by ]O2 was prepared.

[0108] Production Example 3 - Production of Positive Electrode Active Material C Ni 0.6 Co 0.2 Mn 0.2 (OH)2 and LiOH were mixed in amounts such that the molar ratio of (Ni+Co+Mn):Li was 1:1.05. The mixed powder was placed in an alumina crucible and heat-treated at 800°C for 15 hours in an oxygen (O2) atmosphere to obtain Li[Ni 0.6 Co 0.2 Mn 0.2 A positive electrode active material C represented by the formula: ]O2 was produced.

[0109] Production Example 4 - Production of Positive Electrode Active Material D Ni 0.83 Co 0.12 Mn 0.05 (OH)2 and LiOH were mixed in amounts such that the molar ratio of (Ni+Co+Mn):Li was 1:1.05. The mixed powder was placed in an alumina crucible and heat-treated at 850°C for 15 hours in an oxygen (O2) atmosphere to obtain Li[Ni 0.83 Co 0.12 Mn 0.05 A positive electrode active material D represented by ]O2 was produced.

[0110] Production Example 5 - Production of Positive Electrode Active Material E Ni 0.75 Co 0.10 Mn 0.15 (OH)2 and LiOH were mixed in amounts such that the molar ratio of (Ni+Co+Mn):Li was 1:1.05. The mixed powder was placed in an alumina crucible and heat-treated at 800°C for 15 hours in an oxygen (O2) atmosphere to obtain Li[Ni 0.75 Co 0.10 Mn 0.15 A positive electrode active material E represented by ]O2 was produced.

[0111] Production Example 6 - Production of Positive Electrode Active Material F Ni 0.8 Co 0.1 Mn 0.1(OH)2 and LiOH were mixed in amounts such that the molar ratio of (Ni+Co+Mn):Li was 1:1.05. The mixed powder was placed in an alumina crucible and heat-treated at 780°C for 15 hours in an oxygen (O2) atmosphere to obtain Li[Ni 0.8 Co 0.1 Mn 0.1 A positive electrode active material F represented by the formula: ]O2 was produced.

[0112] Production Example 7 - Production of Positive Electrode Active Material G Ni 0.5 Co 0.2 Mn 0.3 (OH)2 and LiOH were mixed in amounts such that the molar ratio of (Ni+Co+Mn):Li was 1:1.05. The mixed powder was placed in an alumina crucible and heat-treated at 900°C for 15 hours in an oxygen (O2) atmosphere to obtain Li[Ni 0.5 Co 0.2 Mn 0.3 A positive electrode active material G represented by ]O2 was produced.

[0113] Average particle size of primary particles The cross section of each of the positive electrode active materials A to G was observed using a scanning electron microscope, and the particle sizes of 100 primary particles in the cross section of the positive electrode active material were measured. The average particle size of the primary particles was then calculated by a method for determining the arithmetic mean value of these particles, and the results are shown in Table 1 below.

[0114] D 50 The powders of the positive electrode active materials A to G were placed in a particle size distribution confirmation device (Microtrac, MT 3000), and ultrasonic waves of about 28 kHz were irradiated at an output of 60 W to obtain a volume cumulative particle size distribution graph. The particle size at the point where the volume cumulative amount is 50% was obtained from the obtained volume cumulative particle size distribution graph. 50 were measured and are shown in Table 1 below.

[0115] [Table 1]

[0116] <Examples and Comparative Examples: Production of Cathode Material> Example 1. The positive electrode active material A prepared in Preparation Example 1 and the positive electrode active material B prepared in Preparation Example 2 were mixed in a weight ratio of 80:20 to prepare a positive electrode material.

[0117] Example 2. The positive electrode active material F prepared in Preparation Example 6 and the positive electrode active material G prepared in Preparation Example 7 were mixed in a weight ratio of 80:20 to prepare a positive electrode material.

[0118] Example 3. The positive electrode active material A prepared in Preparation Example 1 and the positive electrode active material B prepared in Preparation Example 2 were mixed in a weight ratio of 70:30 to prepare a positive electrode material.

[0119] Example 4. The positive electrode active material F prepared in Preparation Example 6 and the positive electrode active material G prepared in Preparation Example 7 were mixed in a weight ratio of 70:30 to prepare a positive electrode material.

[0120] Comparative Example 1 The positive electrode active material A prepared in Preparation Example 1 and the positive electrode active material C prepared in Preparation Example 3 were mixed in a weight ratio of 80:20 to prepare a positive electrode material.

[0121] Comparative Example 2 The positive electrode active material A prepared in Preparation Example 1 and the positive electrode active material D prepared in Preparation Example 4 were mixed in a weight ratio of 80:20 to prepare a positive electrode material.

[0122] Comparative Example 3 Only the positive electrode active material A produced in Production Example 1 was used as the positive electrode material.

[0123] Comparative Example 4 The positive electrode active material A prepared in Preparation Example 1 and the positive electrode active material E prepared in Preparation Example 5 were mixed in a weight ratio of 80:20 to prepare a positive electrode material.

[0124] <Experimental Example> Experimental Example 1: Comparison of c-axis behavior of positive electrode active materials (1) Manufacturing of coin half cells The positive electrode active materials A to G prepared in Preparation Examples 1 to 7 were mixed in N-methylpyrrolidone in a weight ratio of 96:2:2 with a conductive material (carbon black) and a binder (PVDF). The positive electrode slurry was applied to one side of an aluminum current collector, dried at 100°C, and rolled to prepare a positive electrode. An electrode assembly was prepared by interposing a porous polyethylene separator between the positive electrode and the lithium metal negative electrode, and the electrode assembly was placed inside a battery case. An electrolyte was then injected into the case to prepare a coin half cell. The electrolyte was prepared by dissolving LiPF6 at a concentration of 1M in a mixed organic solvent in which ethylene carbonate / dimethyl carbonate / diethyl carbonate were mixed in a volume ratio of 3:4:3.

[0125] (2) Measurement of change in c-axis length The coin half cells to which the positive electrode active materials A to G were applied were disassembled in a glove box in an argon atmosphere to recover the positive electrode, and the positive electrode active materials were sampled using a Be window and a kapton tape. In a state where contact with moisture and air was blocked, an ex-situ XRD analysis was performed to measure the c-axis length (C o ) was measured.

[0126] In addition, each of the prepared coin half cells was charged at 4.2 V against lithium metal at a current density of 20 mA / g, and then the charged cells were disassembled in a glove box under an argon atmosphere to recover the positive electrodes, which were then washed several times with dimethyl carbonate solvent to remove the electrolyte salt. The positive electrode active material was sampled using a Be window and a kapton tape, and an ex-situ XRD analysis was performed in a state where contact with moisture and air was blocked, and the c-axis length (C1) of the positive electrode active material after charging was measured.

[0127] Next, the rate of change in the c-axis length was calculated according to the following formula 1, and is shown in Table 2 below.

[0128] [Formula 1] c-axis length change rate (%) = {(C o -C1 / C o )×100}

[0129] [Table 2]

[0130] From the results in Table 2, it can be seen that the combination of cathode active material F and cathode active material G used in Examples 2 and 4 has the smallest absolute value of the difference in the rate of change in c-axis length, 0.3%.

[0131] (3) Comparison of c-axis behavior during charging and discharging The coin half cell including the prepared cathode active material A and the coin half cell including the prepared cathode active material B were charged to 4.2 V at 0.1 C and discharged to 3.0 V at 0.1 C, and then the change in c-axis length was measured by operando XRD analysis. The graph is shown in FIG. 1.

[0132] As described above, referring to FIG. 1, it can be seen that at the end of charging, positive electrode active material A having a relatively high nickel content experiences a large contraction, whereas positive electrode active material B having a relatively low nickel content exhibits an expanding behavior, and at the beginning of discharging, the opposite behavior is observed.

[0133] Experimental Example 2: Evaluation of life characteristics of batteries using positive electrode material The positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4, conductive material (acetylene black), and PVdF binder were mixed in a weight ratio of 97.5:1.0:1.5 in N-methylpyrrolidone to prepare positive electrode slurries. The positive electrode slurries were applied to one side of an aluminum current collector, which was then dried and rolled to prepare positive electrodes.

[0134] Anode active material (a mixture of natural graphite and artificial graphite in a weight ratio of 50:50), SBR binder, and conductive material (acetylene black) were added to a solvent of water in a weight ratio of 96:1:3 to prepare anode slurry. The anode slurry was applied to a copper thin film as anode current collector, dried, and rolled to prepare anode.

[0135] A polyethylene separator having a thickness of 15 μm was interposed between the positive and negative electrodes to prepare an electrode assembly, which was then inserted into a battery case and an electrolyte was injected to prepare a lithium secondary battery. The electrolyte used was a solution of 1M LiPF6 dissolved in an organic solvent in which ethylene carbonate (EC):ethyl methyl carbonate (EMC) was mixed in a volume ratio of 3:7.

[0136] The lithium secondary battery manufactured as described above was charged at 45° C. at 0.3 C to 4.2 V and discharged at 0.3 C to 2.5 V as one cycle, and the resistance increase rate (DCIR increase) and capacity retention rate (Capacity Retention) were measured while performing 100 cycles of charge and discharge. The measurement results are shown in Table 3 below.

[0137] Here, the resistance increase rate and the capacity retention rate were calculated according to the following formulas 2 and 3.

[0138] [Formula 2] Resistance increase rate (%) = {(resistance after 100 cycles / resistance after 1 cycle) x 100} - 100

[0139] [Formula 3] Capacity retention rate (%) = (discharge capacity after 100 cycles / discharge capacity after 1 cycle) x 100

[0140] [Table 3]

[0141] From the results of Table 3, it can be seen that, as in Examples 1 to 4, the nickel content is relatively high according to the present invention, but the particle size of the primary particles is smaller, and D 50The positive electrode active material A has a lower nickel content but a larger primary particle size, D 50 It can be seen that the use of a positive electrode active material B having a smaller molecular weight is advantageous in improving the battery life and resistance.

[0142] On the other hand, it can be seen that among the Examples, Examples 2 and 4, which use a combination of two positive electrode active materials with a smaller difference in the rate of change in c-axis length, have a higher capacity retention rate and a lower resistance increase rate than Examples 1 and 3.

[0143] In the case of Comparative Example 1, unlike Examples 1 to 4, it can be confirmed that the positive electrode active material C, which has a lower nickel content, has a smaller average particle size of the primary particles than the positive electrode active material A, resulting in decreased capacity and resistance characteristics.

[0144] In Comparative Example 2, positive electrode active materials A and D, both of which had nickel contents of 80 mol% or more, were used, but it was found that the life and resistance characteristics were inferior to those of Examples 1 to 4. Comparative Example 3, in which positive electrode active material A was used alone, showed the worst performance.

[0145] On the other hand, in Comparative Example 4, the nickel content is high, but the particle size of the primary particles is smaller, and D 50 The positive electrode active material A has a lower nickel content but a larger primary particle size, D 50 Even when the positive electrode active material E having a smaller nickel content is used in combination with the positive electrode active material E, when the difference in nickel content is less than 25 mol %, it can be confirmed that the life and resistance characteristics are significantly reduced compared to Examples 1 to 4.

[0146] Experimental Example 3: Measurement of crack area The lithium secondary battery after the evaluation of Experimental Example 2 was disassembled in a glove box under an argon atmosphere to recover the positive electrode, and the cross section of the positive electrode processed by ion milling was observed with a scanning electron microscope to obtain an SEM image of the particle cross section, and the crack area ratio (crack area ratio = crack area / secondary particle area) was calculated by calculating the area of ​​each of the secondary particles and cracks using the concentration difference between them. The calculation results are shown in Table 4 below.

[0147] [Table 4]

[0148] From the results of Table 4, it can be seen that, as in Example 1, the nickel content is relatively high according to the present invention, but the particle size of the primary particles is smaller, and D 50 The positive electrode active material A has a lower nickel content but a larger primary particle size, D 50 It can be confirmed that the use of the positive electrode active material B having a smaller particle size is effective in preventing cracks in the positive electrode active material particles.

[0149] As in the results of Experimental Example 2, it was confirmed that particle cracks occurred in a significantly wider area when a positive electrode active material with a lower nickel content had a smaller average particle size of primary particles (Comparative Example 1), a nickel content difference of less than 25 mol% (Comparative Examples 2 and 4), or when only one positive electrode active material was used alone (Comparative Example 3). It was also confirmed that, among the examples, Examples 2 and 4, which used a combination of two positive electrode active materials with a smaller difference in the rate of change of c-axis length, had a narrower crack occurrence area than Examples 1 and 3.

[0150] That is, it has been experimentally confirmed that the cathode material according to one embodiment of the present invention has the effect of suppressing particle cracks by dispersing stress during charging and discharging, thereby helping to improve the life and resistance characteristics of the battery.

Claims

1. A first positive electrode active material and a second positive electrode active material are included, The first positive electrode active material includes a lithium transition metal oxide having a molar ratio of nickel among transition metals of 70 mol % or more, the second positive electrode active material includes a lithium transition metal oxide in which a molar ratio of nickel among transition metals is 25 mol % or more lower than a molar ratio of nickel among transition metals of the first positive electrode active material; the average particle size of the primary particles constituting the second positive electrode active material is larger than the average particle size of the primary particles constituting the first positive electrode active material, D of the second positive electrode active material 50 is the D of the first positive electrode active material 50 A cathode material for lithium secondary batteries that is smaller than

2. The positive electrode material for lithium secondary batteries according to claim 1, wherein the second positive electrode active material includes a lithium transition metal oxide having a molar ratio of nickel among transition metals of 40 mol% to 65 mol%.

3. 2. The positive electrode material for a lithium secondary battery according to claim 1, wherein the first positive electrode active material comprises a lithium transition metal oxide represented by the following Chemical Formula 1: [Chemical formula 1] Li 1+x (N a Co b Mn c M d )O 2 In the above Chemical Formula 1, M is at least one selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, a, b, c and d are -0.2≦x≦0.2, 0.70≦a<1, 0<b≦0.20, 0<c≦0.20, 0≦d≦0.10, and a+b+c+d=1, respectively.

4. 2. The positive electrode material for a lithium secondary battery according to claim 1, wherein the second positive electrode active material comprises a lithium transition metal oxide represented by the following chemical formula 2: [Chemical formula 2] Li 1+y (N e Co f Mn g M' h )O 2 In the above Chemical Formula 2, M' is at least one selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo; The values ​​of y, e, f, g, and h are -0.2≦y≦0.2, 0.40≦e≦0.65, 0.10≦f≦0.40, 0.10≦g≦0.40, 0≦h≦0.10, and e+f+g+h=1, respectively.

5. 2. The positive electrode material for lithium secondary batteries according to claim 1, wherein the primary particles constituting the first positive electrode active material have an average particle size of 0.1 μm or more and 1 μm or less.

6. 2. The positive electrode material for lithium secondary batteries according to claim 1, wherein the average particle size of the primary particles constituting the second positive electrode active material is greater than 1 μm and less than or equal to 3 μm.

7. D of the first positive electrode active material 50 The positive electrode material for lithium secondary batteries according to claim 1, wherein the thickness of the positive electrode is 8 μm or more and 20 μm or less.

8. D of the second positive electrode active material 50 The positive electrode material for lithium secondary batteries according to claim 1, wherein the thickness is 1 μm or more and less than 8 μm.

9. 2. The positive electrode material for lithium secondary batteries according to claim 1, wherein the absolute value of the difference between the rate of change in c-axis length of the first positive electrode active material according to the following formula 1 and the rate of change in c-axis length of the second positive electrode active material according to the following formula 1 is 0% to 10%. [Formula 1] c-axis length change rate (%) = {(C o -C 1 / C o ) x 100} In the above formula 1, C o is the c-axis length of the positive electrode active material in an uncharged state, C 1 is the c-axis length of the positive electrode active material in a charged state at 4.2 V.

10. 2. The positive electrode material for lithium secondary batteries according to claim 1, wherein the positive electrode material comprises the first positive electrode active material and the second positive electrode active material in a weight ratio of 50:50 to 99:

1.

11. A positive electrode for a lithium secondary battery comprising the positive electrode material for a lithium secondary battery according to any one of claims 1 to 10.

12. A lithium secondary battery comprising the positive electrode for lithium secondary batteries according to claim 11.

Citation Information

Patent Citations

  • Positive electrode active material for secondary battery, method for producing the same, and lithium secondary battery including the same

    JP2021507497A

  • Cathode and electrochemical device

    WO2021012768A1